The AI Revolution in Patient Safety: How Artificial Intelligence Reduces Medical Errors and Saves Lives - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The pursuit of perfect patient care is a constant challenge in modern medicine. Despite the dedication of healthcare professionals, medical errors remain a s...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning